SOME POPULATION PARAMETERS OF BALI SARDINE (Sardinella lemuru) IN BALI STRAIT WATERS - Arief Wujdi (Pusbindiklat - LIPI, 2013)
Purse seine was introduced at 1972 in Bali Strait and since then Bali sardine fish (Sardinella lemuru) are the most widely exploited by fishermen in these waters. One of the largest landing site of Bali Strait purse seiner is in Muncar, East Java. This study aims to estimate population parameters of Bali Strait oil sardine that were caught by purse seine in Muncar. Data were collected from August 2010 to December 2011, and were analyzed using FISAT II (version 1.1.3). The results showed growth parameters were L∞ = 20.75 cmFL; K=1.20 year-1 and t0=0.1456 year. The results of Z=6.39 year-1; M=1.78 year-1; F=4.61 year-1; and E=0.65. The exploitation rate in this study was greater than the optimum exploitation (Eopt), indicating an overfishing had occurred. The recruitment pattern of Bali sardine had two peaks a year, in February and July, where the recruitment in July was greater than February.